2019
DOI: 10.1016/j.jbusres.2019.02.053
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cultural value orientation on consumers' perceptions of luxury value and proclivity for luxury consumption

Abstract: This paper investigates the effect of Schwartz's (1992) four cultural value orientations on the values consumers ascribe to luxury products. In response to well-documented criticisms of assessing cultural values as aggregates measured at the nation level, this study examines the effects of value orientation measured at the individual level. Using survey data from U.S. consumers, the study shows that cultural values influence consumers' perceptions of the usability, uniqueness, quality, and social luxury values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 91 publications
(198 reference statements)
2
57
0
1
Order By: Relevance
“…Thus, academic attention to the Gen Z workforce who are on a fixed employment contracts warrants future investigation. Second, cultural influences are tempered by many macro-contextual factors (Stathopoulou and Balabanis, 2019). The age of interns is a sensitive transition from school to work and thus inevitably suffers from uncertainties (Robinson et al, 2019).…”
Section: Limitations and Recommendations For Future Researchmentioning
confidence: 99%
“…Thus, academic attention to the Gen Z workforce who are on a fixed employment contracts warrants future investigation. Second, cultural influences are tempered by many macro-contextual factors (Stathopoulou and Balabanis, 2019). The age of interns is a sensitive transition from school to work and thus inevitably suffers from uncertainties (Robinson et al, 2019).…”
Section: Limitations and Recommendations For Future Researchmentioning
confidence: 99%
“…Prior research suggests that the appreciation of aesthetic simplicity may be contingent on the perceived status of the product. High‐status brands arguably come with expectations of superior quality, craftsmanship, effort, and originality for example (Ko et al, 2019; Stathopoulou & Balabanis, 2019). According to Stathopoulou & Balabanis (2019, p. 300), the notion of what is luxury (or high status) is also “highly affected by individuals' sense of aesthetics.” In other words, consumers may have different expectations for low‐status versus high‐status brand and therefore evaluate aesthetic complexity differently, which could alter its relationship with product appreciation.…”
Section: Studymentioning
confidence: 99%
“…Product liking and perceived originality do not necessarily have to be correlated, that is, a consumer may like an aesthetically simple product, but not see it as original. Perceived originality as an evaluation criterion may be particularly important for high‐status or exclusive products (Pocheptsova et al, 2010; Stathopoulou & Balabanis, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It can be argued that within their means, the reasons for consumption are based on social comparisons for collectivistic cultures; whereas, in the individualistic cultures, the reasons might be based on self-distinction and hedonic pursuits of self-enhancement reinforced by modernity. For example, in a recent study by Stathopoulou and Balabanis (2019), survey data from U.S. consumers showed that individualistic cultural values influence consumers' "perceptions of the usability, uniqueness, quality, and luxury motives". The study argues that motives of self-enhancement and luxury are the key drivers of consumers' tendency to over-consume luxury brands.…”
Section: Consumption -> Social Image Enhancementmentioning
confidence: 99%